The Role of Tahfidzul Al-Quran Teachers in Forming Student's Religious Character - Ana, Evi; Diah Wahyuningsih; Abdelghani El Rafei (Institut Studi Islam Muhammadiyah Pacitan, 2026)
One innovation that can reduce students' moral problems is the habituation of religious character, namely tahfidzul Al Qur'an. So the author is interested in researching the application of tahfidzul Al Qur'an and the role of tahfidzul Al Qur'an teachers in shaping students' religious character. The aim of this research is to describe the application of tahfidzul Al Qur'an and the role of tahfidzul Al Qur'an teachers in shaping students' religious character. The benefits of research for teachers can be to develop students' religious character in accordance with the teachings of the Islamic religion, for students it can be used as guidance, direction or encouragement to carry out good deeds in accordance with the teachings of Islam, for researchers to develop knowledge and increase insight and knowledge. This research uses a qualitative approach, with data collection techniques using observation, interviews and documentation, taking place at MI Muhamadiyah Kalikuning I with research subjects of 20 students from grades 5 and 6, teachers and school principals. The results of the study concluded that the application of tahfidzul Al-Qur'an to the education of students' religious character is reflected through student behavior, the tahfidzul Al-Qur'an teacher plays a role in shaping students' religious character through the process of forming akhlakul karimah in Islamic religious teachings according to the Qur'an and Hadith.